2009
DOI: 10.1021/bc900425s
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Conjugation at the 5′-End of Oligodeoxynucleotides Abrogates Toll-Like Receptor 9-Mediated Immune Stimulatory Activity

Abstract: Bacterial and synthetic DNA containing unmethylated CpG motifs act as ligands of Toll-like receptor 9 (TLR9). Our earlier studies showed that 5'-accessibility of synthetic oligodeoxynucleotides containing CpG motif (ODN) is required for TLR9-mediated immune stimulatory activity. Blocking the 5'-end of ODN through conjugation to a variety of moieties reduces immune stimulatory activity (Bioconjugate Chem. 2002, 13, 966-974). In the present study, we conjugated a model peptide, a 28-amino-acid-long beta-amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…This enhancement can be explained by the increased resistance of the ODNs to nuclease degradation. Although it has been reported that free 5' ends in CpG ODNs with a PTO backbone are required for the activation of TLR9 [28,29], loss of activity in 5'-modified PD-ODN2006 in this study was attributed to degradation. When we modified PD-ODN2006 with 14-mer oligonucleotides at the 5'-end, there was still some potential to activate NF-κB, with some bands still present after serum degradation.…”
Section: Discussionmentioning
confidence: 62%
“…This enhancement can be explained by the increased resistance of the ODNs to nuclease degradation. Although it has been reported that free 5' ends in CpG ODNs with a PTO backbone are required for the activation of TLR9 [28,29], loss of activity in 5'-modified PD-ODN2006 in this study was attributed to degradation. When we modified PD-ODN2006 with 14-mer oligonucleotides at the 5'-end, there was still some potential to activate NF-κB, with some bands still present after serum degradation.…”
Section: Discussionmentioning
confidence: 62%
“…Together, these results indicate that CpG-B conjugation to NPs led to a higher frequency of activated cross-presenting DCs in the draining LNs, as well as a higher fraction of DCs able to present OVA in a Th1 and CD8 + T-cell-promoting context, for a given dose compared with free CpG-B. Notably, it was previously shown that modifications and conjugation of peptides to the 5′ end of CpG had a tendency to decrease their immunostimulatory effect (33,34). Our 5′ end conjugation strategy between NP and CpG, which allows the latter to be released in the reductive endosomal environment, did not negatively influence the activity of the bound CpG, which were even more stimulatory when conjugated than their free counterparts.…”
Section: Discussionmentioning
confidence: 67%
“…In this study we have used a novel TLR9 agonist containing synthetic immunomodulatory CpR (R = 2′-deoxy-7-dezaguanosine) dinucleotide and 3′-3′-attached novel structures that has been shown to induce potent TLR9-mediated immune responses [18], [19], [20], [21]. The presence of 3′-3′-attached structure provides higher metabolic stability and also optimal 5′-end presentation required for TLR9 recognition [18], [22], [23], [24]. These novel TLR9 agonists have been shown to induce potent Th1-type immune responses and a broad spectrum of antitumor activity in a number of tumor models [18], [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%